A Retrospective Clinical Trial Regarding Oral Rehabilitation Diagnosis Strategies Based on Stomatognathic System Pathology - Lupu, Iulian Costin; Checherita, Laura Elisabeta; Antohe, Magda Ecaterina; Stamatin, Ovidiu; Teslaru, Silvia; Hamburda, Tudor; Tarevici, Eugenia Larisa; Bulancea, Bogdan Petru; Trandafirescu, Mioara; Gena Dascalu, Cristina; Cuciureanu, Magdalena; Gradinaru, Irina; et al. (Biomedicines, 2023)
Introduction: Orofacial pain is a common occurrence in daily dental practice; it is frequently attributed to temporomandibular dysfunction, one of its major causes, followed by pathology of the salivary glands, without avoiding interference at the level of the pain pathways caused by complications of periodontal pathology. The main objective of this study is to identify an important cause of pain in the oral–maxillofacial territory by quantifying the changes at the salivary glandular level using stereological methods. The secondary objective of the present research is to identify the implications of periodontal changes as a consequence of salivary quantitative and qualitative changes, quantified using periodontal indices, on the balance of the temporomandibular joint, dysfunction of it being an important cause of facial pain and having a profound impact on the complex oral rehabilitation algorithm of each clinical case, a condition evaluated with the analysis of the results of the Souleroy questionnaire. Material and methods: In a retrospective study, we evaluated the clinical results obtained after applying complex rehabilitation treatment to 35 subjects, 20 women and 15 men with salivary and TMJ dysfunctions, selected between 2020 and 2021 from the Clinic of Maxillofacial Surgery, Iasi. Results and discussion: The most common symptoms of temporomandibular disorders (TMDs) that were identified through the Souleroy questionnaire were pain and different types of damage to the masticatory muscles. The most significant changes in elders are reported in the case of serous cells, which reduced their percentage volume from 46.7% to 37.4%. Conclusion: As regards stereological analysis in conjunction with histological images, there were significant changes in diameters, perimeters, and longitudinal axes in the adult patients as opposed to the elderly patients, which were also influenced by the type of pathology at this level. The scores recorded on the diagnostic Souleroy scale indicated a large number of patients with low efficiency and maximum stress levels: 20.0% in level 1, 25.7% in level 2, and 25.7% in level 3.